Percepción sobre el acceso a los servicios de salud mental que tienen los residentes de tres municipios de Antioquia, 2004-2006 (2009)
ABSTRACT: To know the perception of users, family, health providers and staff on mental health services and access conditions in three municipalities. Methodology: The information was extracted from users, family members, providers and officials. It includes medical and social gaze from an ethnographic approach. We interviewed 29 citizens in the sectors of health, educational, social and judicial. Results: the description of mental health problem is different in the three municipalities, both in its pathological dimension as causal explanations, because causation is attributed to social violence and working conditions. The results showed that difficulties in providing services, but also highlights some positive aspects. Post-Trauma Violence is common in the municipalities but the triggers are specific to humans. Discussion: In addition to mental disorders, psychosocial problems are also related to mental health. Among the difficulties of access, it was found affiliation to the Social Security System, financial resources and scarce qualified personnel.